Green hemostatic sponge-like scaffold composed of soy protein and chitin for the treatment of epistaxis. (June 2022) - Jimenez-Martin, Jon; Las Heras, Kevin; Etxabide, Alaitz; Uranga, Jone; de la Caba, Koro; Guerrero, Pedro; Igartua, Manoli; Santos-Vizcaino, Edorta; Hernandez, Rosa Maria
Abstract: Epistaxis is one of the most common otorhinolaryngology emergencies worldwide. Although there are currently several treatments available, they present several disadvantages. This, in addition to the increasing social need of being environmentally respectful, led us to investigate whether a sponge-like scaffold (SP–CH) produced from natural by-products of the food industry — soy protein and β-chitin — can be employed as a nasal pack for the treatment of epistaxis. To evaluate the potential of our material as a nasal pack, it was compared with two of the most commonly used nasal packs in the clinic: a basic gauze and the gold standard Merocel®. Our SP-CH presented great physicochemical and mechanical properties, lost weight in aqueous medium, and could even partially degrade when incubated in blood. It was shown to be both biocompatible and hemocompatible in vitro, clearing up any doubt about its safety. It showed increased blood clotting capacity in vitro, as well as increased capacity to bind both red blood cells and platelets, compared to the standard gauze and Merocel®. Finally, a rat-tail amputation model revealed that our SP-CH could even reduce bleeding time in vivo . This work, carried out from a circular economy approach, demonstrates that a green strategy can be followed to manufacture nasal packs using valorized by-products of the food industry, with equal or even better hemostatic properties than the gold standard in the clinic. Graphical abstract: Image 1